SISTEM INFORMASI PENGENDALIAN INTERN ATAS PIUTANG UNTUK MEMINIMALKAN JUMLAH PIUTANG TAK TERTAGIH PADA KSU MAKMUR MANDIRI MENGGUNAKAN METODE UMUR PIUTANG - Edy Siswanto; Mifthahurrahman (UNIVERSITAS STEKOM, 2020)
KSU Makmur Mandiri is a business-store cooperative located in the village of Yosorejo Rt. 03 Rw. 03, Gringsing District, Batang Regency and was established on August 14, 2008 with the Legal Entity Number 518.21 / 142 / BH / XIV / VIII / 08. This cooperative in conducting more operations do credit transaction or credit sales rather than savings, in this case the credit sales of the company has a large amount of receivables, in the transaction receivables are often still a lot of troubled receivables, are due but still not pay, the existence of bad debts that accumulate. The absence of internal controls on accounts receivable causes many problems in report generation. The calculation of the amount of receivables is still manual, so it takes a long time to obtain the data and there is no debtor loan history. The Company requires internal control of the receivables, to obtain accurate information on the troubled receivables, the action that a company can take is to prepare the criteria for the length of the receivables, which until now can not be collected, using the age method of receivables based on the period of time. The purpose of this research is to design an information system with age method of receivables, to receivables that have matured but have not paid and calculate the amount of bad debts, and age of delay of receivables quickly and accurately.